2005
DOI: 10.1159/000087942
|View full text |Cite
|
Sign up to set email alerts
|

Potential Protective Effects of NSAIDs/ASA in Oxidatively Stressed Human Lens Epithelial Cells and Intact Mouse Lenses in Culture

Abstract: Purpose: To study possible toxic effects of indomethacin, diclofenac, and celecoxib (NSAIDs) and acetylsalicylic acid (ASA) as well as potentially protective effects of these substances in oxidatively stressed human lens epithelial cells (HLEC) and in intact mouse lenses in culture. Methods: HLEC and mouse lenses were incubated with NSAIDs or ASA alone or in the presence of H2O2. To study apoptosis the cells were then either stained with Hoechst 33342 or assayed for caspase-3 activity. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 62 publications
(39 reference statements)
2
14
0
Order By: Relevance
“…It is considered that H 2 O 2 , a major oxidant, contributes to cataract formation [22] . In a previous study, we found that low concentrations of the nonselective COX-1 and COX-2 inhibitors indomethacin and diclofenac, the selective COX-2 inhibitor celecoxib and ASA protected against hydrogen peroxide-induced apoptosis in human lens epithelial cells (HLECs) [23] . Higher concentrations of NSAIDs ( 1 0.5 M ) or ASA ( 1 30 m M ) induced apoptosis in itself, which further emphasizes that both protective and toxic effects of NSAIDs/ASA can be seen depending on the concentration used.…”
Section: Introductionmentioning
confidence: 94%
“…It is considered that H 2 O 2 , a major oxidant, contributes to cataract formation [22] . In a previous study, we found that low concentrations of the nonselective COX-1 and COX-2 inhibitors indomethacin and diclofenac, the selective COX-2 inhibitor celecoxib and ASA protected against hydrogen peroxide-induced apoptosis in human lens epithelial cells (HLECs) [23] . Higher concentrations of NSAIDs ( 1 0.5 M ) or ASA ( 1 30 m M ) induced apoptosis in itself, which further emphasizes that both protective and toxic effects of NSAIDs/ASA can be seen depending on the concentration used.…”
Section: Introductionmentioning
confidence: 94%
“…Many stimuli that cause oxidative stress are sufficient to induce apoptosis through the mitochondrial pathway. Previous studies have demonstrated that caspase-3 plays a key role in the HLE cell apoptosis induced by oxidative stress [10,[12][13][14], suggesting a mitochondria-mediated signaling pathway is involved. In addition, in vitro studies have identified caspase-9, Apaf1 and cytochrome c as participants in a complex important for caspase-3 activation [25], and there is reduced apoptosis in caspase-9 deficient mice [26].…”
Section: Parthenolide Suppressed the Activation Of Caspase-3 And Caspmentioning
confidence: 99%
“…Elevated levels of H 2 O 2 are reported in the aqueous humor of cataract patients [8], and both internal and external sources of oxidative stress induce LEC apoptosis and cause lens opacification in vitro [9][10][11]. Although the detail signaling pathways involved are still unclear, caspase-3 has been shown to play a key role in the lens epithelial cell apoptosis induced by oxidative stress [10,[12][13][14]. In addition, a previous study Parthenolide inhibits lens cell apoptosis 566 npg has suggested that aB-crystallin, a molecular chaperon, can prevent LEC from apoptosis through inhibition of activation of caspase-3 [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,21 The concentration of glutathione, a tripeptide thiol decreases with age in the lens and more markedly in cataracts. 22,24 An approach to glutathione level inside the lens by its increased synthesis or decreased breakdown was tried by some groups using agents acting against glutathione. The potential role of vitamins and antioxidants in preventing various diseases is well documented.…”
Section: Discussionmentioning
confidence: 99%